Strategies Employed in Time Management in Online Modality Learning as Perceived By Grade 12 HUMSS Students at Bestlink College of the Philippines: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Time management is one of the best ways to overcome these stresses caused by multi-functionality. This study assesses the strategies employed by selected students for them to manage their time as they conquer their academic journey. The researchers surveyed 60 students from Grade 12 HUMSS of Bestlink College of the Philippines. Methodological statistics were used to accumulate and tabulate the survey results using the Likert Scale. This study revealed that distractions, procrastination and unorganized planning were the common problems the respondents faced that caused them to struggle to handle their time properly. This study recommends that respondents and future researchers dig deeper into time planning and focus on assembling things based on their importance. Lastly, researchers recommend that the general public eliminate uncertainties and distractions to ensure a well-managed time.
Keywords: Strategies employed; Online Modality Learning; Perceived